Estimation of Internal Solitary Waves Propagation Speeds and Occurrence Using Long-Term Sentinel-1 SAR Data in the Lombok Strait, Indonesia - Chonnaniyah; Abd. Rahman As-Syakur; I Made Dharma Raharja; Takahiro Osawa (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Synthetic aperture radar (SAR) data are necessary for ocean observations and useful for detecting internal solitary waves (ISWs). Sentinel-1 provides free and open data access and offers valuable long-term datasets for ISW studies. The Lombok Strait is well known for its large ISW amplitude in SAR images. This strait is an outflow for the Indonesian Throughflow, which plays a crucial role in global thermohaline circulation. A nine-year dataset of Sentinel-1 SAR imagery in the Lombok Strait areas was utilized for the first time to analyze the occurrence frequency detection and propagation speed estimation of ISWs. This study proposes combining information from Sentinel-1 images with tidal predictions from a model to estimate the propagation speed of ISWs in the Lombok Strait. Correlation analysis revealed a moderate positive relationship between ISW occurrence and the Indian Ocean Dipole (IOD) index (0.365), while the El Niño–Southern Oscillation (ENSO) index had a negligible influence (–0.006). For ISW propagation speeds, there was moderate negative correlation with ENSO (–0.30) and a weak negative correlation with the IOD (–0.18), suggesting that ENSO-related changes in ocean stratification have a stronger impact on ISW propagation. Fast Fourier Transform analysis identified a 54-month cycle of ISW occurrence and a 12-month cycle of propagation speed, highlighting the effects of long-term climatic oscillations and seasonal patterns on ISW dynamics. This research demonstrates the utility of remote sensing techniques, such as SAR, in detecting ISW surface signatures, although biases remain compared to in situ measurements due to limitations in temporal resolution and environmental factors.